The economic life of a small community during the Covid-19 pandemic in the Simalingkar A area of North Sumatra - Adawiyah, Rodiatun; Prasetyo, Muhammad Arif; Ayu, Hanuring; Sirait, Ricky Evelina; Ginting, Febby Paska Regina Br; Tarigan, Gabrena Batu Sitta Yesyurun (Priviet Social Sciences Journal, 2022)
Two years ago, discovery of Covid-19. This virus is transmitted through the air, thats why we are always asked to wear a mask when not at home. Therefore, the Government has implemented the restrictions on community activities (PPKM) due to the increasing number of COVID-19 cases, so people have to work from home. This makes it difficult for people who run small businesses to earn an income. This  study  aims  to  determine  the  impact of Covid-19 on the economy of people with lower income in Simalingkar A and to find out how the government took steps to overcome this. This study uses a naturalistic method carried out in natural conditions with a descriptive qualitative approach by explaining several questions through interviews. The conclusion of this study is that only a few lower class people have been affected by the economic impact of Covid-19 and the government made a program, BLT UMKM, (Permenkop No. 2 of 2021) and Pre-employment programs as a solution. However, there are still people who have not received assistance from the program, so that we as researchers hope that the governmeniont can pay more attention to its people during the economic crisis of Covid-19 Pandemic.